THE EFFECT OF PUZZLE GAME TOWARDS STUDENT'S VOCABULARY MASTERY AT THE EIGHTH GRADE STUDENTS OF MTS TANWIRUL KUTUB BAYAH LEBAK – BANTEN IN ACADEMIC YEAR 2021/2022 - Musa Musa; Riandi Riandi; Rizdki Elang Gumelar (Journal of English Language Teaching and Literature (JELTL), 2023)
In learning English, one of the language components that should be acquired by students is vocabulary. It is the element that connects the four English skills such as listening, speaking, reading, and writing. The objective of the research is to find out is there any significant of Puzzle Game towards student's vocabulary mastery at the eighth grade students of MTs Tanwirul Kutub Bayah. In this method, the researcher uses a quasi-experimental method with two groups the experimental class and the control class.The population of the research is all the eighth grade students of MTS Tanwirul Kutub Bayah which consisted of 2 classes, with a total of 66 with a sample of 33 students in class VIII A and class VIII B as many as 33 students. The instrument for collecting quantitative data was a pre-test and a post-test with a total of 25 questions. The Researcher calculated data by using SPSS 2.2. Based on the analysis using paired samples test, it can be concluded that t-count= -7.430 and signification value (p-value) = 0.000 < α = 0.05, so H1 is accepted and H0 is rejected. On the other word, there is a significant effect of puzzle game towards Student's vocabulary mastery.